2020
DOI: 10.3390/rs12040646
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sheep Activity from Tri-Axial Acceleration Signals Using a Moving Window Classification Model

Abstract: Behaviour is a useful indicator of an individual animal’s overall wellbeing. There is widespread agreement that measuring and monitoring individual behaviour autonomously can provide valuable opportunities to trigger and refine on-farm management decisions. Conventionally, this has required visual observation of animals across a set time period. Technological advancements, such as animal-borne accelerometers, are offering 24/7 monitoring capability. Accelerometers have been used in research to quantify animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 26 publications
3
32
0
3
Order By: Relevance
“…The problem of imbalanced data is, of course, not unique to the behavior of pigs, but is also seen in the behavior of cows (Homburger et al, 2014), calves (Abell et al, 2017), sheep (Fogarty et al, 2020), and goats (Sakai et al, 2019). Barwick (2020) used an imbalanced dataset directly as the training set to identify sheep activity from triaxial acceleration signals. Their results showed that lying behavior was predicted very poorly from the collar data with a sensitivity of 6%, since limited lying behavior was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem of imbalanced data is, of course, not unique to the behavior of pigs, but is also seen in the behavior of cows (Homburger et al, 2014), calves (Abell et al, 2017), sheep (Fogarty et al, 2020), and goats (Sakai et al, 2019). Barwick (2020) used an imbalanced dataset directly as the training set to identify sheep activity from triaxial acceleration signals. Their results showed that lying behavior was predicted very poorly from the collar data with a sensitivity of 6%, since limited lying behavior was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Under-sampling has the drawback that when observations are removed from the majority class, potentially useful information is lost. The drawback of the commonly used simple over-sampling is that a large number of identical samples will be generated, which will cause the model to over-fit to those repeated observations (Barwick, 2020). In the field of livestock science, most researchers who address the problem of imbalanced data sets do so by applying the under-sampling solution (e.g., Smith et al, 2016;Abell et al, 2017;Sakai et al, 2019;Fogarty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete events of individual behaviours were annotated to reflect the mutually exclusive behaviours of licking, eating, standing and lying ( Table 1 ). The software time-stamped the beginning and the end of each event over a particular time regardless the type animals [ 6 , 10 , 31 ]. Each event was processed only if the cattle performed an observed behaviour for a minimum duration of 10 s to avoid multiple events merged in one epoch.…”
Section: Methodsmentioning
confidence: 99%
“…Wireless technology using animal-borne sensors allows individual animals to be physically monitored in real-time without interfering in their natural behaviour [ 6 , 7 ]. Tri-axial accelerometers have been routinely deployed to automatically record and classify behaviours of domesticated animals based on the acceleration movements over the three perpendicular axes [ 8 , 9 , 10 , 11 ]. Recent investigations have reported that tri-axial accelerometers were capable of categorising oral and intake behaviours of ruminants such as suckling [ 12 ], ruminating, eating [ 13 ], grazing [ 14 ], chewing, biting [ 11 ], and drinking [ 15 ].…”
Section: Introductionmentioning
confidence: 99%